2018
DOI: 10.18332/tid/95159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a natural polyphenol on nicotine-induced pancreatic cancer cell proliferation

Abstract: INTRODUCTION Resveratrol ( trans -3, 4’, 5-trihydroxystilbene), a phytoalexin derived from the skin of grapes and other fruits, has anti-inflammatory and anti-oxidant effects. Its anti-carcinogenic effects are closely associated with its antioxidant activity; thus, the use of resveratrol as a possible cancer chemo-preventive is considered to be an important area of investigation. In this study we have examined the inhibitory effects of resveratrol in nicotine induced pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…To test whether nicotine was active in the cell growth media and cell culture condition using the DMEM supplemented with 2 mM L-glutamine, we treated A549 lung cancer cells with the nicotine (2 or 10 μM) or the vehicle control (0 μM nicotine) for 48 hours. It has been reported that nicotine can activate the Erk in multiple cell lines via promotion of the Erk phosphorylation [40][41][42][43][44][45]. We found that nicotine indeed induced Erk1/2 phosphorylation in A549 cells as shown in Fig 2 , suggesting that nicotine was active in the cell culture media DMEM supplemented with 2 mM L-glutamine.…”
Section: Resultssupporting
confidence: 61%
“…To test whether nicotine was active in the cell growth media and cell culture condition using the DMEM supplemented with 2 mM L-glutamine, we treated A549 lung cancer cells with the nicotine (2 or 10 μM) or the vehicle control (0 μM nicotine) for 48 hours. It has been reported that nicotine can activate the Erk in multiple cell lines via promotion of the Erk phosphorylation [40][41][42][43][44][45]. We found that nicotine indeed induced Erk1/2 phosphorylation in A549 cells as shown in Fig 2 , suggesting that nicotine was active in the cell culture media DMEM supplemented with 2 mM L-glutamine.…”
Section: Resultssupporting
confidence: 61%
“…RES has been attributed multiple beneficial properties such as being an antioxidant, a free radical scavenger and increasing longevity [ 32 , 33 , 41 , 74 ]. However, very few studies have examined if RES could modulate the effects of NIC [ 49 51 ]. Moreover, the effect of RES on the putative genotoxic effect of NIC has not been studied in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Only a few in vitro studies have examined whether NIC’s effects could be modulated by RES. There is evidence that RES can protect against NIC-induced oxidative damage in renal tubule cells [ 49 ] Leydig cells [ 50 ], and against NIC-induced proliferation of pancreatic cells [ 51 ]. A couple in vivo studies in rats showed that RES reduces NIC-induced changes in the lungs [ 52 ], and NIC-induced renal impairment after chronic NIC exposure [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine represents the most toxic factor of tobacco, may lead to excessive cell proliferation through an increase in oxidative stress, and also has been related to an improvement of the invasiveness of lung and breast cancer cells ( Bose et al, 2005 ; Dasgupta et al, 2009 ). Resveratrol prevents nicotine-induced cell proliferation through the MAPK signaling pathway by means of the downregulation of p-ERK in pancreatic cells ( Chowdhury et al, 2018a ). Alcohol consumption has been related to the development of colorectal cancer ( Nishihara et al, 2014 ).…”
Section: Polyphenols: Their Chemistry and Their Importance In Human Healthmentioning
confidence: 99%